DEVELOPMENT OF MORAL-CULTURAL RELATIONSHIPS IN STUDENTS IN RUSSIAN LANGUAGE CLASSES (MULTIDISCIPLINARY JOURNAL: FUNDAMENTAL RESEARCH SCIENTIFIC JOURNAL, 2025)
This article explores effective methods and pedagogical approaches aimed at fostering and developing students' moral and cultural attitudes while learning Russian. The authors view Russian as a powerful tool not only for mastering communication skills but also as a foundation for nurturing the younger generation in the spirit of universal values, cultural traditions, and civic responsibility. The article analyzes the role and importance of Russian language lessons in introducing students to the richness of Russian literature, history, and culture, as well as in fostering their appreciation of the importance of respecting language as a national treasure. It emphasizes that through mastering grammar, vocabulary, syntax, and stylistics, students gain the ability not only to express their thoughts correctly but also to understand the deep meanings embedded in works of literary art.